Risk factors for atopic diseases and recurrent respiratory tract infections in children. Issue 11 (15th September 2020) - Kansen, Hannah M.; Lebbink, Melanie A.; Mul, Joeri; van Erp, Francine C.; van Engelen, Martine; de Vries, Esther; Prevaes, Sabine M. P. J.; Le, Thuy My; van der Ent, Cornelis K.; Verhagen, Lilly M.
Abstract: Introduction: The simultaneously increased prevalence of atopic diseases and decreased prevalence of infectious diseases might point to a link between the two entities. Past work mainly focused on either atopic diseases or recurrent infections. We aim to investigate whether risk factors for atopic diseases (ie, asthma, allergic rhinitis, atopic dermatitis, and/or food allergy) differ from risk factors for recurrent respiratory tract infections (RRTIs) in children. Methods: Cross‐sectional data were used from 5517 children aged 1 to 18 years who participated in an Electronic Portal for children between 2011 and 2019. Univariable/multivariable logistic regression analyses were performed to determine risk factors for any atopic disease and RRTIs. Results: Children aged ≥5 years were more likely to have any atopic disease (adjusted odds ratio [OR]: 1.50‐2.77) and less likely to have RRTIs (OR: 0.68‐0.84) compared to children aged less than 5 years. Female sex (OR: 0.72; 95% confidence interval [CI]: 0.63‐0.81), low birth weight (OR: 0.74; 95% CI: 0.57‐0.97) and dog ownership (OR: 0.79; 95% CI: 0.66‐0.95) reduced the odds of any atopic disease, but not of RRTIs. Daycare attendance (OR: 1.22; 95% CI: 1.02‐1.47) was associated with RRTIs, but not with atopic diseases. A family history of asthma, allergic rhinitis, atopic dermatitis, and RRTIs was significantly associated with the same entity in children, with OR varying from 1.58 (95% CI: 1.35‐1.85) in allergic rhinitis to 2.20 (95% CI: 1.85‐2.61) in asthma. Conclusion: Risk factors for atopic diseases are distinct from risk factors for RRTIs, suggesting that the changing prevalence of both entities is not related to shared risk factors.